Cry Dance: An Emmett Parker and Anna Turnipseed Mystery (Emmett Quanah Parker mysteries, 1, 1)
If there's one thing that Bureau of Indian Affairs Investigator Emmett Quanah Parker knows, it's that the dead don't always stay dead. With him he carries the ghosts of a partner killed in action, three failed marriages, and a long affair with the bottle. And now he's about to face the most dangerous case of his career—one that begins with a body that doesn't stay buried. The corpse of a woman, brutally murdered and bizarrely mutilated, is discovered on Havasupai Nation land. Parker is paired with FBI Special Agent Anna Turnipseed in a hastily assembled task force of two. The two share a mixed Native American ancestry—and little else. As they are pulled deeper into a complex case, Parker suspects they are being led, like Custer to a Little Bighorn, into a killer's trap. At the heart of it are the dead, and history is the most lethal weapon of all. Fans of Tony Hillerman will enjoy these novels by Kirk Mitchell, whose background as a sheriff on a reservation brings an exciting realism to the books.

Dance of the Thunder Dogs (Emmett Quanah Parker mysteries, 5, 1)
After thirteen years of federal law enforcement assignments that took him to every Indian nation but his own, Emmett Parker has come home to Oklahoma on convalescent leave, badly wounded and estranged from his partner and love interest, Anna Turnipseed. At once a son of the Comanche people and a government investigator for the Bureau of Indian Affairs, he has ties to both sides—and is about to discover which side pulls harder. On the reservation, Emmett finds an intricate web of familial and tribal duties—and what could become a massive class action suit. Indian plaintiffs are suing the BIA for oil well funds they never received. Drawn into the controversy, Emmett is accused of murder by an investigator of his own blood. Now, the man who used to be the law is running from it.

Firestorm (Anna Pigeon mysteries, 4, 1, 1996)
A raging forest fire in California's Lassen Volcanic National Park traps exhausted firefighters, including Ranger Anna Pigeon, in its midst. Afterward, Anna finds two from her group have been killed. One a victim of the flames. The other, stabbed through the heart. Now, as a rampaging winter storm descends, cutting the survivors off from civilization, Anna must uncover the murderer in their midst.

Ill wind (Anna Pigeon mysteries, 3, 1, 2019)
In this breathtaking suspense novel by Nevada Barr, park ranger Anna Pigeon is faced with a sinister mystery that threatens the visitors of Mesa Verde. As a strange and deadly disease spreads through the park, Anna must unravel the source and put an end to the evil wind that carries it. With gripping twists and turns, Ill Wind transports readers to the atmospheric landscape of Mesa Verde, immersing them in the heart-pounding action as Anna races against time to uncover the truth. Fans of Nevada Barr's thrilling storytelling and gripping mysteries won't be able to put this book down.

Endangered species (Anna Pigeon mysteries, 5, 1, 2008)
Tough, likable park ranger Anna Pigeon is back in another high-spirited outdoors adventure/mystery. Anna has been assigned a three-week posting on Georgia's isolated Cumberland Island. Despite the breathtaking natural setting, Anna finds time weighing heavily as she works tedious fire pre-suppression duty. Her boring routine is shattered when a sudden plane crash in the inland palmetto thickets calls her and the other members of the fire crew to action.  When Anna and the crew investigate, they discover the plane was sabotaged. Suspicions smolder over the accident which killed both the pilot and his passenger, Cumberland's lone law enforcement ranger. Even the usually unflappable Anna is shocked by the desperate cold-bloodedness of the crime. Will protecting the island come at a price even Anna is unwilling to pay?

Track of the Cat (Anna Pigeon mysteries, 1, 1, 1997)
THE FIRST ANNA PIGEON NOVEL—WINNER OF THE AGATHA AWARD. The fascinating hero of Nevada Barr’s award-winning series—park ranger Anna Pigeon—has brought an unyielding love of nature and sense of fair play to the mystery genre. Track of the Cat is the acclaimed novel that first introduced readers to Anna, as a woman looking for peace in the wilderness—and finding murder instead…   Patrolling the remote West Texas backcountry, Anna’s first job as a national park ranger is marred by violence she thought she had left behind: the brutal death of a fellow ranger. When the cause of death is chalked up to a mountain lion attack, Anna’s rage knows no bounds. It’s up to her to save the protected cats from the politics and prejudices of the locals—and prove the kill was the work of a species far less rare…

Blind Descent: An Anna Pigeon Novel Series, Book 6 (Anna Pigeon mysteries, 6, 1, 1998)
Park ranger Anna Pigeon is enjoying the open spaces of Colorado when she receives an urgent call. A young woman has been injured while exploring a cave in New Mexico?s Carlsbad Cavern Park. Before she can be pulled to safety, she sends for her friend Anna. Only one problem: a crushing fear of confined spaces has kept Anna out in the open her whole life.

A Superior Death (Anna Pigeon mysteries, 2, 1, 1998)
Park ranger Anna Pigeon returns, in a mystery that unfolds in and around Lake Superior, in whose chilling depths sunken treasure comes with a deadly price. In her latest mystery, Nevada Barr sends Ranger Pigeon to a new post amid the cold, deserted, and isolated beauty of Isle Royale National Park, a remote island off the coast of Michigan known for fantastic deep-water dives of wrecked sailing vessels. Leaving behind memories of the Texas high desert and the environmental scam she helped uncover, Anna is adjusting to the cool damp of Lake Superior and the spirits and lore of the northern Midwest. But when a routine application for a diving permit reveals a grisly underwater murder, Anna finds herself 260 feet below the forbidding surface of the lake, searching for the connection between a drowned man and an age-old cargo ship. Written with a naturalist's feel for the wilderness and a keen understanding of characters who thrive in extreme conditions, A Superior Death is a passionate, atmospheric page-turner.

Liberty Falling (Anna Pigeon mysteries, 7, 1, 2010)
Anna Pigeon is in Manhattan to look after her hospitalized sister, and explores the Statue of Liberty in her spare time. But when a teenage girl falls to her death from Liberty's ledge, Anna wonders if the suicide was actually a homicide-and begins an investigation that puts her in the line of fire.

Blood Lure (Anna Pigeon mysteries, 9, 1, 2000)
In this mystery in Nevada Barr’s New York Times bestselling series, District Park Ranger Anna Pigeon is betrayed by nature itself, as a most unnatural evil stalks its prey in the pristine West… Straddling the border between Montana and Canada lies the Waterton-Glacier International Peace Park—Anna’s home away from home when she is sent on a cross-training assignment to study grizzly bears. Along with bear researcher Joan Rand and a volatile, unpredictable teenage boy, Anna hikes the back country, seeking signs of bear. But the tables are turned on their second night out, when one of the beasts comes looking for them. Daybreak finds the boy missing, a camper mutilated, and Anna caught in a grip of fear, painfully aware that her lifelong bond with nature has inexplicably snapped...

Deep South (Anna Pigeon mysteries, 8, 1, 2000)
Nevada Barr's ever-popular Anna Pigeon series is consistently praised as "exceptional" (Denver Post), "stunning" (Seattle Times), and "superb" (New York Times Book Review). In Deep South, Park Ranger Anna Pigeon heads to Mississippi, only to encounter terrible secrets in the heart of the south… Anna Pigeon finally gives in to her bureaucratic clock-and signs on for a promotion. Next thing she knows, she's knee-deep in mud and Mississippi. Not exactly what she had in mind. Almost immediately, as the new district ranger on the Natchez Trace, Anna discovers the body of a young prom queen near a country cemetery, a sheet around her head, a noose around her neck. It's a bizarre twist on a best-forgotten past of frightening racial undertones. As fast as the ever-encroaching kudzu vines of the region, the roots of this story run deep-and threaten to suffocate anyone in the way, including Anna...

Spirit sickness (Emmett Quanah Parker mysteries, 2, 1, 2000)
In the tradition of Tony Hillerman and Joseph Wambaugh comes Kirk Mitchell's latest suspense thriller, which reunites Bureau of Indian Affairs Criminal Investigator Emmett Quanah Parker and FBI Special Agent Anna Turnipseed, two Native American cops torn between their heritage and the law. A fire-gutted police cruiser found in a remote part of the Navajo reservation bears the bodies of a tribal patrolman and his wife. Parker and Turnipseed know a cop's murder is never simple, raising countless questions and suspicions. When another murder is discovered, the case explodes into an otherworldly realm. Both Parker, a Comanche, and Turnipseed, a Modoc, are well acquainted with the eerie shadow land between native myth and modern homicide investigation. Now they will have to touch minds with a murderer who has woven personal madness with Navajo myth to create his own reality—and with it, the need to kill and kill again.

Hunting season (Anna Pigeon mysteries, 10, 1, 2002)
Park Ranger Anna Pigeon returns to face her most duplicitous foe—human nature—in Nevada Barr's New York Times bestseller, Hunting Season.   The quiet beauty of autumn on Mississippi’s Natchez Trace is swiftly shattered when Anna answers a call to Mt. Locust, once a working plantation and inn, now a tourist spot. But the man Anna finds in an old bedroom is no tourist in distress. He’s nearly naked, and very dead—his body bearing marks consistent with sex games gone awry. On a writing table nearby is an open Bible with ominous passages circled in red.   There are secrets that prominent men in this God-fearing country wish to keep under wraps—and Anna has stumbled into a nest of them.

Flashback (Anna Pigeon mysteries, 11, 1, 2003)
The five-week New York Times bestseller, now in paperback. Running from a proposal of marriage from Sheriff Paul Davidson, Anna Pigeon takes a post as a temporary supervisory ranger on remote Garden Key in Dry Tortugas National Park, a small grouping of tiny islands in a natural harbor seventy miles off Key West. This island paradise has secrets it would keep; not just in the present, but in shadows from its gritty past, when it served as a prison for the Lincoln conspirators during and after the Civil War. Here, on this last lick of the United States, in a giant crumbling fortress, Anna has little company except for the occasional sunburned tourist or unruly shrimper. When her sister, Molly, sends her a packet of letters from a great-great-aunt who lived at the fort with her husband, a career soldier, Anna's fantasy life is filled with visions of this long-ago time. When a mysterious boat explosion-and the discovery of unidentifiable body parts-keeps her anchored to the present, Anna finds crimes of past and present closing in on her. A tangled web that was woven before she arrived begins to threaten her sanity and her life. Cut off from the mainland by miles of water, poor phone service, and sketchy radio contact, and aided by one law-enforcement ranger, Anna must find answers or weather a storm to rival the hurricanes for which the islands are famous.

High country (Anna Pigeon mysteries, 12, 1, 2005)
It's fall in the Sierra Mountains, and Anna Pigeon is slinging hash in Yosemite National Park's historic Ahwahnee Hotel. Four young people, all seasonal park employees, have disappeared, and two weeks of work by crack search-and-rescue teams have failed to turn up a single clue; investigators are unsure as to whether the four went AWOL for reasons of their own - or died in the park. Needing an out-of-park ranger to work undercover, Anna is detailed to dining room duty; but after a week of waiting tables, she knows the missing employees are only the first indication of a sickness threatening the park. Her twenty-something roommates give up their party-girl ways and panic; her new restaurant colleagues regard her with suspicion and fear. Yet when Anna's life if threatened and her temporary supervisor turns a deaf ear, she follows the scent of evil, taking a solo hike up a snowy trial to the high country, seeking answers. What awaits her is a nightmare of death and greed - and perhaps her final adventure.

Hard truth (Anna Pigeon mysteries, 13, 1, 2006)
Just days after marrying Sheriff Paul Davidson, Anna Pigeon moves to Colorado to assume her new post as district ranger at Rocky Mountain National Park. When two of three children who'd gone missing from a religious retreat reappear, Anna's investigation brings her face-to-face with a paranoid sect—and with a villain so evil, he'll make the hairs on the back of your neck stand on end.

Sky Woman Falling: An Emmett Parker and Anna Turnipseed Mystery (Emmett Quanah Parker mysteries, 4, 1, 2006)
FBI Special Agent Anna Turnipseed, a Modoc Indian from California, and Bureau of Indian Affairs Investigator Emmett Parker, a Comanche from Oklahoma, are a team, sent by the Feds wherever there are problems in tribal territory. This assignment takes them to upstate New York where Brenda Two Kettles, an elder of the Oneida tribe, was found dead in a cornfield, every major bone in her body shattered. She seems to have fallen from the sky, like Sky Woman of the Oneida creation myth. When Anna and Emmett discover that Brenda was the center of a bitter land dispute between Indians and whites, they are sure she was murdered. Their investigation brings them face to face with the dangers of race war, and soon their own lives depend on Anna’s instincts and her ability to see the line where myth and reality come together.

Winter Study (Anna Pigeon mysteries, 14, 1, 2008)
Soon after Anna Pigeon joins the famed wolf study team of Isle Royale National Park in the middle of Lake Superior, the wolf packs begin to behave in peculiar ways. Giant wolf prints are found, and Anna spies the form of a great wolf from a surveillance plane. When a female member of the team is savaged, Anna is convinced they are being stalked, and what was once a beautiful, idyllic refuge becomes a place of unnatural occurrences and danger beyond the ordinary…

Ancient Ones: An Emmett Parker and Anna Turnipseed Mystery (Emmett Quanah Parker mysteries, 3, 1, 2009)
Though there are signs of foul play, BIA investigator Emmett Quanah Parker and FBI special agent Anna Turnipseed aren't looking for a killer—the remains dug out of a riverbank by an illegal fossil hunter are fourteen thousand years old. Parker and Turnipseed are sent to Central Oregon as official witnesses to the examination of John Day Man, as he is dubbed, for the bones have quickly provoked a controversy that threatens to erupt into violence: the skeleton is distinctly Caucasian, not Native American, shattering long-held tenets concerning who the first inhabitants of this continent were. Emmett, with his Comanche and white ancestry, and Anna, a reservation-born Modoc with Asian blood, share a sensitivity to both parties' concerns—and a forbidden attraction that's causing them professional and personal problems. As a result, they are too distracted by each other to see the escalating suspicion and fear around them when a young tribal anthropologist is swallowed by the misty night and within hours of her disappearance the fossil hunter who discovered the skeleton is found disemboweled. The Warm Springs Indians insist that the unburied bones of the Ancient One have been turned into askep, a murderous spirit that haunts the darkness. As winter closes in on the steppes of the Columbia Plateau, accusations of ritualized murder fly between the Indian and white communities—and the fight turns deadly when a second skeleton is unearthed. In the midst of the turmoil, Emmett and Anna are paralyzed by their own demons. This estrangement could prove deadly if they stop watching each other's back long enough for a killer to target them too. And at the center of it all are the Ancient Ones, exacting a terrible price as the dark path to resolution runs a gauntlet through the boneyards of prehistory.

Borderline (Anna Pigeon mysteries, 15, 1, 2009)
The New York Times bestseller starring Anna Pigeon from the author of Winter Study. “Action-packed…a narrative that plunges readers into mystery [and] mayhem.”—The Denver Post Hoping a raft trip in Big Bend National Park will lift her spirits, Anna Pigeon and her husband Paul go to southwest Texas, where the Rio Grande is running high. The beauty of the Chihuahuan Desert and the power of the river work their magic—until the raft is lost in the rapids and a young college student makes a grisly discovery. Caught in a strainer between two boulders—and more dead than alive—is a pregnant woman. Anna will soon discover that nature isn’t the only one who wants to see the woman and her baby dead…